Breaking the Silence is Personal, Political, and Collective - Bonomini Martínez, Sandra (2024)
Eliana Monteiro holds an MA in Performing Arts from Universidad de São Paulo (USP), and she has been Teatro da Vertigem’s director for the past 26 years. She is a theater educator and art/performance festivals curator. Her most recent work as a director includes the following productions: Intervención Florestania, Autoexamen de cuerpo de delito, and Levante, a project about love and resistance in lesbian women’s couples throughout Brazil’s recent history.